RCT of post-conflict trauma interventions in the Central African Republic - William John Froming; Maryke Van Zyl; Karen Bronk Froming; Vicky Bouche; Sita G. Patel (Cambridge Prisms: Global Mental Health, 2025)
This study evaluates mental health treatment in a post-conflict setting with scant mental health resources. The study reports on a randomized crossover control group design with one intervention and two control groups implemented in the Central African Republic (CAR).